High‐Specificity In Vivo Tumor Imaging Using Bioorthogonal NIR‐IIb Nanoparticles. Issue 49 (7th October 2021) - Luo, Zichao; Hu, Dehong; Gao, Duyang; Yi, Zhigao; Zheng, Hairong; Sheng, Zonghai; Liu, Xiaogang
Abstract: Lanthanide‐based NIR‐IIb nanoprobes are ideal for in vivo imaging. However, existing NIR‐IIb nanoprobes often suffer from low tumor‐targeting specificity, limiting their widespread use. Here the application of bioorthogonal nanoprobes with high tumor‐targeting specificity for in vivo NIR‐IIb luminescence imaging and magnetic resonance imaging (MRI) is reported. These dual‐modality nanoprobes can enhance NIR‐IIb emission by 20‐fold and MRI signal by twofold, compared with non‐bioorthogonal nanoprobes in murine subcutaneous tumors. Moreover, these bioorthogonal probes enable orthotopic brain tumor imaging. Implementation of bio‐orthogonal chemistry significantly reduces the nanoprobe dose and hence cytotoxicity, providing a paradigm for real‐time in vivo visualization of tumors. Abstract : Bioorthogonal lanthanide‐based nanoprobes are developed for deep‐tissue NIR‐IIb imaging and MRI with high tumor‐targeting specificity. These bioorthogonal nanoprobes offer a 20‐fold increase in the NIR‐IIb imaging signal and a 2‐fold increase in the MRI signal, compared with non‐orthogonal probes.